Management - Robbins, Stephen P.; Coulter, Mary (Boston, Massachusetts : Pearson, 2014)
This book doesn't just describe management theories ; it brings them to life!
The world of management -- Managing in the twenty-first century -- Making decisions and managing change -- Planning and control -- Organizing -- Leading
Includes index.
Keywords: MANAGEMENT